STRATEGIC INTEGRATION OF FINANCIAL WELLNESS IN HUMAN RESOURCE PRACTICES: ENHANCING EMPLOYEE RESILIENCE AND ORGANIZATIONAL PERFORMANCE - Syarkani, Yofy (Branding: Jurnal Manajemen dan Bisnis, 2023)
In the face of increasing economic uncertainty, organizations are confronted with the rising prevalence of employee financial stress, which adversely affects workplace productivity, engagement, and retention. This article explores the strategic role of Human Resource Management (HRM) in integrating financial wellness programs as a vital component of employee support systems. Drawing from multidisciplinary theoretical frameworks such as the Conservation of Resources Theory and the Job Demands-Resources Model, this study synthesizes findings from previous research on the implementation of financial literacy education, payroll-based assistance, and mental health interventions aimed at strengthening employee financial resilience. The analysis highlights how financial wellness initiatives contribute not only to individual stability and adaptive capacity but also to broader organizational outcomes such as improved performance, reduced turnover, and enhanced employer branding. This article provides a conceptual foundation for viewing financial wellness as a strategic imperative within HR practices, offering practical implications for policy formulation and future research on sustainable workforce management in a volatile economic landscape.